Teachers’ Self-Efficacy and Teacher-Initiated Parental Involvement: The Two-Tier Lens on Teachers’ Performance - Maldia, Sheryl Manarin (Future Science / FSH-PH Publications, 2024)
This study examined the relationship between teachers’ self-efficacy, teacher-initiated parental involvement, and their impact on the performance of elementary teachers in DepEd SDO Sto. Tomas City. A total of 261 public elementary school teachers participated, using a descriptive correlational design to assess the variables through a survey questionnaire. Results showed that teachers rated their self-efficacy as